Forest Law Harmony: Bridging the Gap between Forest Area Utilization Agreements (PPKH) and Land Ownership Certificates (Sertifikat Tanah) in Land Ownership with Penal Mediation Approaches - Rahmani Rahmani; Muhammad Hadin Muhjad (Jurnal Syntax Transformation, 2023)
This article explores conflicts from overlapping forest lands allocated through Indonesia's Forest Area Utilization Agreements (PPKH) with occupied customary lands lacking legal ownership certificates. Companies and forest communities often clash over ancestral tenure rights. Mediation balances economic growth, social justice, and environmental sustainability. The paper examines efforts to bridge regulatory gaps between PPKH licensing and Land Ownership Certificates (Sertifikat Tanah) through penal mediation in Indonesian Borneo. Comparative case studies analyze mediation techniques, shaping legal certainty, sustainable land use, governance, and benefit-sharing outcomes. Mediated agreements resulted in formal permit adjustments and land titles for 20,000 hectares, providing legal security. Settlements enhanced social equity through shared employment, profits, and infrastructure. Success factors include participatory mapping, company financing for bureaucratic procedures, leveraging customary institutions, and embedding multi-stakeholder oversight. Partial shortcomings highlight the need for further policy and power structure reforms to fully realize mediation potential in balancing nationwide forest land conflicts.